Beryllium in riverine/estuarine sediments from a typical aquaculture wetland, China: Bioavailability and probabilistic ecological risk. (December 2018) - Gu, Yang-Guang; Wang, Liang-Gen; Gao, Yan-Peng
Abstract: Beryllium (Be) is of a significant concern because of its mutagenic and carcinogenic properties. However, reports on presences of Be in sediments from aquaculture areas still remain unknown. This study investigated the total concentration and bioavailability of Be in the surface sediments from Rongjiang River and its estuary in a large-scale aquaculture wetland in Chaoshan metropolis, South China; together with its probabilistic ecological risks posed to aquatic organisms. The total and bioavailable concentrations of Be were in the range of 5.11–8.02 and 0.23–0.33 mg/kg, respectively. Total concentration of Be mainly originated from anthropogenic source and bioavailable Be was <6% of the total concentration of Be. The probabilistic ecological risk assessment based on bioavailable concentration of Be showed that surface sediments of Rongjiang River and its estuary had a low (2.91%) probability of toxic effect to aquatic organisms. Graphical abstract: Highlights: Total and bioavailable Be in sediments from an aquaculture wetland area were analyzed. Total Be concentration was higher than other world locations. Be had <6% of bioavailability. Sediments had a 2.91% probability of toxic effect derived from bioavailable Be.